Enhancing Turbine Output at Dry-Cooled Power Plants Using a Hybrid (Dry/Wet) Dephlegmator. Issue 11 (13th August 2017) - Owen, Michael; Kröger, Detlev; Reuter, Hanno
ABSTRACT: This paper examines the benefits to steam turbine output of retrofitting an air-cooled steam condenser with a hybrid (dry/wet) dephlegmator (HDWD) in a coal-fired, reheat, regeneration cycle. A hybrid dephlegmator concept has been proposed and shown to provide enhanced air-cooled condenser cooling performance while consuming only a small amount of water. The hybrid dephlegmator retrofit is shown to be able to increase turbine power output by up to 10.8% in certain cases. A corresponding increase in annual energy output of 2.56% can be achieved for continuous wet operation of the hybrid dephlegmator. A likely operating scenario, where hybrid dephlegmator units are sequentially operated in wet mode in order to maintain rated turbine power output over a wide range of ambient temperatures, results in an annual energy output increase of 1.33%. Based on these results, the payback period for an HDWD retrofit is between 3 and 6 years. The hybrid dephlegmator concept offers a simple, cost-effective, and sustainable solution to the issue of reduced air-cooled condenser performance at high ambient temperatures and is capable of providing clean dispatchable power.